Design and fabrication of polydimethylsiloxane based low cost microfluidic for ultra-fast diagnostic applications - Balakrishnan S.R.; Hashim U.; Sahrim M.; Ismail I.; Jamaludin J.; Ismail W.Z.W.; Perumal V.; Haarindraprasad R.; Mahalingam S. (Penerbit UTHM, 2024)
Indexed by WOS/SCOPUS/ERA